Fancy Bioisosteres: Novel Paracyclophane Derivatives as Super-Affinity Dopamine D3 Receptor Antagonists - Gmeiner, Peter; Hübner, Harald; et al. (Journal of Medicinal Chemistry, 2006)
The exploration of the chemical diversity space depends on the discovery of novel bioisosteric elements. As a continuation of our project on bilayered arene surrogates, we herein report on [2.2]paracyclophane-derived dopamine D3 receptor antagonists of type 4 and 6. For the most promising test compound 6a, bearing a 2-methoxyphenyl substituent, a stereocontrolled preparation was performed when the planar chirality of enantiomers (R)-6a (FAUC 418) and (S)-6a caused a considerable differentiation of D3 binding, which is indicated by Ki values of 0.19 and 3.0 nM, respectively. Functional experiments showed D3 antagonist properties for the paracyclophane derivatives of type 6. To elucidate putative bioactive low-energy conformations, DFT-based studies including the calculation of diagnostic magnetic shielding properties were performed. An 89% increase in volume for the [2.2]paracyclophane moiety compared to that of the monolayered benzofurane of lead compound 3b indicates higher plasticity of GPCR binding regions than usually expected. © 2006 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2006.nat.dchph.lphch.fancyb